The Chloride Homeostasis of CA3 Hippocampal Neurons Is Not Altered in Fully Symptomatic Mepc2-null Mice - Belaïdouni, Yasmine; Diabira, Diabe; Zhang, Jinwei; Graziano, Jean-Charles; Bader, Francesca; Montheil, Aurelie; Menuet, Clément; Wayman, Gary A.; Gaiarsa, Jean-Luc (Frontiers in Cellular Neuroscience, 2021)
Rett Syndrome (RTT) is an X-linked neurodevelopmental disorder caused mainly by mutations in the MECP2 gene. Mouse models of RTT show reduced expression of the cation chloride cotransporter KCC2 and altered chloride homeostasis at presymptomatic stages. However, whether these alterations persist to late symptomatic stages has not been studied. Here we assess KCC2 expression and chloride homeostasis in the hippocampus of early (postnatal (P) day 30-35) and late (P50-60) symptomatic male Mecp2-null (Mecp2-/y ) mice. We found (i) no difference in the relative amount, but an over-phosphorylation, of KCC2 and NKCC1 between WT and Mecp2-/y hippocampi and (ii) no difference in the inhibitory strength, nor reversal potential, of GABAA-receptor mediated responses in Mecp2-/y CA3 pyramidal neurons compared to WT at any stages studied. Altogether, these data indicate the presence of a functional chloride extrusion mechanism in Mecp2-/y CA3 pyramidal neurons at symptomatic stages.